2021
DOI: 10.1016/j.heliyon.2021.e06399
|View full text |Cite
|
Sign up to set email alerts
|

Fungal and metabolome diversity of the rhizosphere and endosphere of Phragmites australis in an AMD-polluted environment

Abstract: Symbiotic associations with rhizospheric microbial communities coupled with the production of metabolites are key adaptive mechanisms by metallophytes to overcome metal stress. However, little is known about pseudometallophyte Phragmites australis interactions with fungal community despite commonly being applied in wetland phytoremediation of acid mine drainage (AMD). In this study, fungal community diversity and metabolomes production by rhizosphere and root endosphere of P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 81 publications
1
13
0
Order By: Relevance
“…In our study, Ascomycota was a dominant and widespread phylum in all seed-borne fungal communities of different oat seeds. Our results demonstrated the earlier findings on Phragmites australis (Ernst et al, 2003), Elymus nutans (Guo et al, 2020), and Phragmites australis (Kalu et al, 2021), which showed this phylum as a common and dominant phylum. A total of 10 most abundant genera in different oat seeds were Alternaria, Mycosphaerella, Epicoccum, Cladosporium, Pyrenophora, Fusarium, Bipolaris, Guehomyces, Aspergillus, Stemphylium, and Nigrospora, respectively.…”
Section: Seed-borne Fungal Community Compositionsupporting
confidence: 91%
“…In our study, Ascomycota was a dominant and widespread phylum in all seed-borne fungal communities of different oat seeds. Our results demonstrated the earlier findings on Phragmites australis (Ernst et al, 2003), Elymus nutans (Guo et al, 2020), and Phragmites australis (Kalu et al, 2021), which showed this phylum as a common and dominant phylum. A total of 10 most abundant genera in different oat seeds were Alternaria, Mycosphaerella, Epicoccum, Cladosporium, Pyrenophora, Fusarium, Bipolaris, Guehomyces, Aspergillus, Stemphylium, and Nigrospora, respectively.…”
Section: Seed-borne Fungal Community Compositionsupporting
confidence: 91%
“…Acidea extrema, Acidiella bohemica, Acidiella uranophila, Acidomyces acidophilus, Acidomyces acidothermus, Acidothrix acidophila, Coniochaeta fodinicola, Hortaea acidophila, and Soosiella minima are fungal species has reported to be enriched in acidic habitat (Selbmann et al, 2008;Vázquez-Campos et al, 2014). Most recently, Kalu et al (2021) revealed Ascomycota and Basidiomycota as the dominant phyla in two gold mining sites in Gauteng Province of South Africa using high-throughput sequencing technology. Prasanna et al (2011) also reported the enrichment of AMD with algal communities such as Euglena sp.…”
Section: Microbial Community Diversity Under Amd Habitatsmentioning
confidence: 99%
“…Another noteworthy study is that of Brereton et al (2020) which cataloged the rhizosphere microbiome of Festuca arundinacea, Salix miyabeana and Medicago sativa in contaminated soil. In addition, Kalu et al (2021) investigated the fungal and metabolome diversity of rhizosphere and endosphere of P. australis in an acid minepolluted environment. Furthermore, Mang and Ntushelo (2021) investigated the influence of acid mine water on the diversity and metabolite shift of microbial populations of the common reed.…”
Section: Microbial Consortia Associated With Phragmites Australis In Environmental Remediationmentioning
confidence: 99%